2024
DOI: 10.3390/app14051945
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Manufacturing of Screw-Shaped Parts in Screw Compressors

Yongfei Wang,
Linhua Xiong,
Dongxiao Feng
et al.

Abstract: Screw compressors are highly researched and developed prospects in industry because of their long service life, high transmission efficiency, low footprint and low vibration. As the key core part of the screw compressor, the screw is a typical, long-shaft, complex profile part. Its processing method, manufacturing accuracy and quality have an extremely important impact on the performance of the whole screw compressor. In this work, the research progress on the manufacturing of screw-shaped parts in screw compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Hydrogen has the characteristics of an extremely high energy density, wide production method, and environmental friendliness, and it is suggested that it will replace fossil energy [1]. Hydrogen can also be used as a long-term energy storage medium to offset the disadvantages of randomness and volatility of solar energy, wind energy, and other green energy sources [2,3]. Therefore, hydrogen fuel is regarded as an important energy carrier in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen has the characteristics of an extremely high energy density, wide production method, and environmental friendliness, and it is suggested that it will replace fossil energy [1]. Hydrogen can also be used as a long-term energy storage medium to offset the disadvantages of randomness and volatility of solar energy, wind energy, and other green energy sources [2,3]. Therefore, hydrogen fuel is regarded as an important energy carrier in the future.…”
Section: Introductionmentioning
confidence: 99%